A method for preparing renewable energy from biomass in wastewater by photothermal decomposition
Through the light thermal cracking method, the coal gangue and load-type cracking catalysts are used to collaborate with the collaborative cracking of sludge within the temperature range of 500-550 ° C. Renewable energy for aromatics.
Patent Information
- Application Number
- CN202411604474.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Under severe weather conditions, it is difficult to maintain stable solar heating at 700°C, resulting in unstable thermal cracking product composition and decreased CH4 and aromatic hydrocarbon content.
After using the light thermal cracking method, after dehydration and crushing the sludge, add coal gangue and load cracked catalyst (铈-锆 锆 solid-soluble body load NI) to coordinate the cracking within the temperature range of 500-550 ° C, and use the common solution objects And catalyst promotes the stability of products and the production of high -value energy.
Under severe weather conditions, the proportion of CH4 in gas phase products is more than 70%, and the proportion of aromatic hydrocarbons in liquid phase products is stable at more than 85%, which increases the yield and stability of renewable energy.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of sludge treatment, and in particular to a method for preparing renewable energy from biomass in wastewater by photothermal decomposition. Background Art
[0002] In the process of sewage treatment, the generation of biomass (sludge) in sewage is a common problem. In the biological treatment unit, the microorganisms added to the treatment equipment will proliferate and form biomass in the process of decomposing organic matter in sewage. This part of biomass cannot be completely degraded in the sewage treatment process and can only be discharged from the system in the form of sludge. With the acceleration of urbanization and the increase in industrial sewage discharge, the treatment capacity of sewage treatment plants has been continuously improved, resulting in a corresponding increase in the amount of sludge generated. However, the treatment and disposal of sludge requires a lot of energy and resources, including dehydration, drying, stabilization, disinfection and other processes. These processes are not only energy-intensive, but also require a lot of capital investment. Therefore, in order to achieve economical treatment, people have proposed a new idea of treating sludge as a biomass and converting it into renewable energy (such as CH4, aromatics) through anaerobic digestion, thermal cracking, gasification and other technologies, so as to achieve energy recovery, material circulation and sludge resource utilization.
[0003] Among many new sludge treatment technologies, thermal cracking technology has high adaptability to the source and properties of biomass in sewage, and has high recycling efficiency for both urban and industrial wastewater sludge. It can also flexibly adjust process parameters according to different needs and conditions to maximize resource utilization. Therefore, thermal cracking has become the most promising biomass treatment technology in sewage. Thermal cracking is a treatment technology that requires heating to achieve. In order to save energy and implement the concept of resource utilization, technicians have adopted a solar energy absorption and storage combined device to continuously supply heat for thermal cracking technology. As we all know, solar heating is very test of environmental conditions (such as local temperature, humidity, wind speed, etc.). Under extreme weather conditions, although the heating temperature has been set at the confirmed value of 700°C (at this time, the content of CH4 and aromatics in the product is high), solar heating may not be able to be stably maintained at 700°C due to bad weather conditions. The cracking environment with a temperature of less than 700°C will lead to unstable composition of cracking products and a decrease in the content of CH4 and aromatics in the product.
[0004] Therefore, under the premise that weather conditions are force majeure factors, how to ensure that the composition of cracking products is more stable in order to obtain more high-value energy (CH4 and aromatics) has become a problem that needs to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, the present application provides a method for preparing renewable energy from biomass in wastewater by photothermal decomposition.
[0006] The present application provides a method for preparing renewable energy from biomass in wastewater by photothermal decomposition, comprising the following steps: dehydrating and crushing the sludge to obtain a starting material, adding a co-solvent and a supported cracking catalyst, mixing them evenly and heating them to 500-550°C, collecting gaseous products and liquid products escaping from the system, and obtaining renewable energy after separation, wherein the weight ratio of the starting material, the co-solvent and the supported cracking catalyst is 80:(10-12):(25-30), the co-solvent includes coal gangue, the carrier in the supported cracking catalyst is a cerium-zirconium solid solution, the main catalytic substance is Ni, and the loading rate of Ni is 12-13wt%, and the cerium-zirconium solid solution is prepared by the following method:
[0007] Disperse Zr(NO3)4·5H2O and Ce(NO3)3·6H2O in a molar ratio of (3-9):1 in water, and add them together with ammonia water into a polyethylene glycol solution under stirring to stabilize the pH value in the system at 10.5-11.5, stir, add ethanol, and heat to 65-75°C at a heating rate of 2-2.2°C / min, continue stirring, then keep the temperature unchanged, age, filter, wash, freeze-dry, and calcine to obtain a cerium-zirconium solid solution.
[0008] Among them, the concentration of the polyethylene glycol solution is 40wt%, the solution is ethanol, and the solute is PEG-4000. The concentration and solute can be routinely adjusted by those skilled in the art according to actual conditions. This application only uses the above parameters and substances as examples for illustration, and does not limit the scope of protection of this application accordingly.
[0009] The method for preparing the supported cracking catalyst comprises the following steps:
[0010] Ni(NO3)2·6H2O, anhydrous citric acid and ethylene glycol are dispersed in water, ultrasonically mixed to obtain a mixed solution, and the mixed solution is uniformly added to the cerium-zirconium solid solution by an equal volume impregnation method. After standing at room temperature, the temperature is increased, the standing is continued, the temperature is increased, and the catalyst is calcined to obtain a supported cracking catalyst with a Ni loading rate of 12-13wt%.
[0011] By adopting the above-mentioned technical scheme, the present application utilizes coal gangue as a co-solvent to carry out photothermal cracking together with the starting material. The mineral components inside the coal gangue can promote the conversion of complex organic matter in the starting material into volatile organic matter first, and finally produce a CH4-rich gas phase product and an aromatic hydrocarbon-rich liquid phase product. In addition, the coal gangue itself is a waste, and its recycling also has the significance of resource treatment. The cerium-zirconium solid solution loaded with Ni is also used as a loaded cracking catalyst to promote the methanation reaction in the system. The catalyst has a high selectivity for CH4, which greatly increases the CH4 content in the gas phase product, and at the same time increases the rate of the thermal cracking reaction process, so that the resource treatment efficiency of biomass in sewage during the treatment cycle can be maintained at a high level. On this basis, the present application controls the temperature range in the photothermal cracking process to 500-550°C. Compared with the high temperature of 700°C, within this temperature range, solar heating can maintain the temperature through its own heat storage function even in severe weather, thereby achieving a good and stable heating effect. The co-solvent can still maintain a high level of CH4 in the gas phase product and aromatic hydrocarbons in the liquid phase product. More importantly, the supported cracking catalyst of the present application can maintain catalytic activity and stability far exceeding other catalysts when the temperature fluctuates, thereby stabilizing the reaction degree of the cracking reaction in the system and improving the yield of aromatic hydrocarbons and CH4 together with the co-solvent.
[0012] In summary, the present application utilizes the co-solvent and the starting material to carry out synergistic photothermal cracking under the catalysis of a supported cracking catalyst. Under the premise of a temperature range of 500-550°C, the proportion of CH4 in the gas phase product is still stabilized at more than 70%, and the proportion of aromatics in the liquid phase product is still stabilized at more than 85%.
[0013] Preferably, the weight ratio of the starting material, the co-lysate and the supported cracking catalyst is 80:11:28.
[0014] By adopting the above technical scheme, the present application strictly controls the weight ratio of the starting material, the co-solvent and the supported cracking catalyst, further improving the yield of CH4 and aromatics. Under this weight ratio, the proportion of CH4 in the gas phase product can reach 74.9%, and the proportion of aromatics in the liquid phase product can reach 88.6%.
[0015] Preferably, the molar ratio of Zr(NO3)4·5H2O to Ce(NO3)3·6H2O is 4:1.
[0016] By adopting the above technical scheme, the present application strictly controls the molar ratio of Zr(NO3)4·5H2O and Ce(NO3)3·6H2O, thereby controlling the molar ratio of Zr and Ce in the final cerium-zirconium solid solution. At this time, the specific surface area of the cerium-zirconium solid solution is large, and the metal-support interaction is most moderate, which greatly improves the sintering resistance of the supported cracking catalyst during the reaction process, thereby further improving the catalytic stability of the supported cracking catalyst, and can continuously play a good catalytic effect on the methanation reaction, maintaining the CH4 content in the gas phase product at a stable high level.
[0017] Preferably, the supported cracking catalyst further comprises an auxiliary catalytic substance with a loading rate of 0.6-1.0 wt %, and the auxiliary catalytic substance comprises Mg and La in a molar ratio of (0-6): (0-6).
[0018] By adopting the above technical solution, the present application adds a certain loading rate of auxiliary catalytic material to the supported cracking catalyst, broadens the reaction activity temperature range of the supported cracking catalyst, and further improves its adaptability to temperature and reaction activity.
[0019] Preferably, the auxiliary catalytic material comprises Mg and La in a molar ratio of (1-3):(2-6).
[0020] Preferably, the molar ratio of Mg to La is 2:4.
[0021] By adopting the above technical scheme, the present application uses Mg and La as auxiliary catalytic substances, and the two can give full play to the synergistic effect, maximize the catalytic activity of the supported cracking catalyst, and at the same time further expand the reaction activity temperature range of the supported cracking catalyst. When temperature fluctuations occur during the cracking process, the catalytic effect can be made more stable, and the yield of aromatics and CH4 can be kept stable and high. Experimental data show that when the molar ratio of Mg to La is 2:4, the synergistic effect of the two is the best, and the proportion of aromatics and CH4 in the product can reach the highest value.
[0022] Preferably, the loading rate of the auxiliary catalytic substance is 0.72wt%.
[0023] By adopting the above technical solution, the present application strictly controls the loading rate, thereby improving the catalytic ability of the loaded cracking catalyst. If the loading rate is too high, it will affect the catalytic effect of Ni, and if the loading rate is too low, it will not have an effective auxiliary effect.
[0024] Preferably, the co-solvent comprises coal gangue and calcined coal gangue in a weight ratio of 5:(2-3).
[0025] Preferably, the weight ratio of the coal gangue to the calcined coal gangue is 5:2.8.
[0026] By adopting the above technical solution, the present application adds a certain amount of calcined coal gangue to the co-solvent, and when cracked together with the starting material, the calcined coal gangue has a more significant effect of promoting the formation of aromatics than the uncalcined coal gangue. The co-solvent composed of a certain weight ratio of coal gangue and calcined coal gangue can further enhance its own effect of promoting the formation of aromatics and increase the proportion of aromatics in the liquid phase product.
[0027] At the same time, the present application further controls the weight ratio of coal gangue to calcined coal gangue to 5:2.8, so that the co-solvent's promotion effect on CH4 and aromatics reaches an optimal balance, and both are at a high level, and at this time the synergistic effect of the co-solvent and the supported cracking catalyst is better, so that the proportion of CH4 and aromatics generated in the product is further improved.
[0028] In summary, this application has the following beneficial technical effects:
[0029] 1. The present application utilizes the co-solvent and the starting material to carry out synergistic photothermal cracking under the catalysis of a supported cracking catalyst, and under the premise of a temperature range of 500-550°C, the proportion of CH4 in the gas phase product is still stabilized at more than 70%, and the proportion of aromatics in the liquid phase product is stabilized at more than 85%;
[0030] 2. The present application adds a certain loading rate of auxiliary catalytic substances to the supported cracking catalyst, broadens the reaction activity temperature range of the supported cracking catalyst, further improves its adaptability to temperature, and strictly controls the loading rate. Mg and La are used together as auxiliary catalytic substances, so that the proportion of aromatics and CH4 in the product is further increased;
[0031] 3. The present application adds a certain amount of calcined coal gangue to the co-solvent, so that the co-solvent can further enhance its own promoting effect on the formation of aromatics and increase the proportion of aromatics in the liquid phase product. DETAILED DESCRIPTION
[0032] Material Source
[0033] Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically:
[0034] Zr(NO3)4·5H2O, Ce(NO3)3·6H2O, Ni(NO3)2·6H2O, La(NO3)3·6H2O, and Mg(NO3)2·6H2O were purchased from Tianjin Guangfu Fine Chemical Research Institute and were of analytical grade;
[0035] Ammonia water was purchased from Shandong Feisheng Chemical Co., Ltd., industrial grade ammonia water, with a concentration of 25wt%;
[0036] PEG-400 was purchased from Jining Tangyi Chemical Co., Ltd., CAS No. 25322-68-3;
[0037] Anhydrous citric acid was purchased from Henan Yilu Chemical Technology Co., Ltd. with a density of 1.542 g / cm 3 , CAS number is 77-92-9;
[0038] The coal gangue was provided by the local mining area and ground to 50um for use. Its composition is shown in Table 1.
[0039] Table 1.1 Composition of coal gangue
[0040]
[0041] The calcined coal gangue is as follows: the ground coal gangue is placed in a muffle furnace, calcined at 700°C for 60 minutes, and cooled to room temperature;
[0042] Sludge is the residue of urban sewage, and its specific components are shown in Table 1.2;
[0043] Table 1.2 Sludge composition
[0044]
[0045] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.
[0046] Preparation Example 1.1
[0047] The preparation method of the supported cracking catalyst comprises the following steps:
[0048] I. Preparation of cerium-zirconium solid solution: using a soft film plate-coprecipitation method, first disperse 8 mol Zr(NO3)4·5H2O and 2 mol Ce(NO3)3·6H2O in 20 L of water, and add them together with ammonia water into 20 L of 40 wt% PEG-400 ethanol solution under stirring, stabilize the pH value in the system at 10.5-11.5 with ammonia water, stir at room temperature for 2 h, add 6 L of anhydrous ethanol, heat to 75°C at a heating rate of 2.2°C / min, continue stirring for 3 h, then keep the temperature unchanged, age for 24 h, filter, wash, freeze-dry, and calcine at 600°C for 3 h to obtain a cerium-zirconium solid solution;
[0049] II. Preparation of catalyst: Ni(NO3)2·6H2O, anhydrous citric acid and ethylene glycol are dispersed in water to obtain a mixed solution with a Ni(NO3)2·6H2O concentration of 3.4 mol / L and anhydrous citric acid concentration of 4.08 mol / L, 0.8 wt% of ethylene glycol is added, ultrasonic mixing is performed for 10 min, and then the adsorption volume of the cerium-zirconium solid solution obtained in step I on the mixed solution is measured by an equal volume impregnation method, and an equal adsorption volume of the mixed solution is added dropwise to the cerium-zirconium solid solution obtained in step I, and the temperature is raised to 75°C after standing at room temperature for 24 h, and the mixture is continued to stand for 6 h to allow complexation to occur in the system, and then the mixture is heated to 120°C at a heating rate of 2°C / min and dried for 12 h, and finally the mixture is heated to 450°C at a heating rate of 2°C / min and calcined for 3 h to obtain a supported cracking catalyst with a Ni loading rate of 12 wt%.
[0050] Preparation Example 1.2
[0051] The preparation method of the supported cracking catalyst comprises the following steps:
[0052] I. Preparation of cerium-zirconium solid solution: using a soft film plate-coprecipitation method, first disperse 9 mol Zr(NO3)4·5H2O and 1 mol Ce(NO3)3·6H2O in 20 L of water, and add them together with ammonia water into 20 L of 40 wt% PEG-400 ethanol solution under stirring, stabilize the pH value in the system at 10.5-11.5 with ammonia water, stir at room temperature for 2 h, add 6 L of anhydrous ethanol, heat to 65°C at a heating rate of 2°C / min, continue stirring for 3 h, then keep the temperature unchanged, age for 24 h, filter, wash, freeze-dry, and calcine at 600°C for 3 h to obtain a cerium-zirconium solid solution;
[0053] II. Preparation of catalyst: Ni(NO3)2·6H2O, anhydrous citric acid and ethylene glycol are dispersed in water to obtain a mixed solution with a Ni(NO3)2·6H2O concentration of 3.4 mol / L and anhydrous citric acid concentration of 4.08 mol / L, 0.8 wt% of ethylene glycol is added, ultrasonic mixing is performed for 10 min, and then the adsorption volume of the cerium-zirconium solid solution obtained in step I on the mixed solution is measured by an equal volume impregnation method, and an equal adsorption volume of the mixed solution is added dropwise to the cerium-zirconium solid solution obtained in step I, and the temperature is raised to 75°C after standing at room temperature for 24 h, and the mixture is continued to stand for 6 h to allow complexation to occur in the system, and then the mixture is heated to 120°C at a heating rate of 2°C / min and dried for 12 h, and finally the mixture is heated to 450°C at a heating rate of 2°C / min and calcined for 3 h to obtain a supported cracking catalyst with a Ni loading rate of 12.5 wt%.
[0054] Preparation Example 1.3
[0055] The preparation method of the supported cracking catalyst is different from that of Preparation Example 1.1 in that: in step I, the amount of Zr(NO3)4·5H2O used is 7.5 mol, the amount of Ce(NO3)3·6H2O used is 2.5 mol, and the rest is the same as Preparation Example 1.1.
[0056] Preparation Example 1.4
[0057] The preparation method of the supported cracking catalyst is different from that of Preparation Example 1.1 in that: in step I, the amount of Zr(NO3)4·5H2O used is 8.5 mol, the amount of Ce(NO3)3·6H2O used is 1.5 mol, and the rest is the same as Preparation Example 1.1.
[0058] Preparation Example 2.1
[0059] The preparation method of the supported cracking catalyst is different from that of Preparation Example 1.1 in that, in step II, an auxiliary catalytic substance with a loading rate of 0.6 wt % is also included, specifically:
[0060] II. Preparation of catalyst: Ni(NO3)2·6H2O, La(NO3)3·6H2O, anhydrous citric acid and ethylene glycol were dispersed in water to obtain a mixed solution with a Ni(NO3)2·6H2O concentration of 3.4 mol / L, a La(NO3)3·6H2O concentration of 0.17 mol / L and anhydrous citric acid concentration of 4.284 mol / L. The amount of ethylene glycol added was 0.84 wt%. Ultrasonic mixing was performed for 10 min. Then, the isovolumetric impregnation method was used to measure the content of the catalyst in step I. The adsorption volume of the obtained cerium-zirconium solid solution on the mixed solution is added dropwise to the cerium-zirconium solid solution obtained in step I, and the mixture is allowed to stand at room temperature for 24 hours, and then the temperature is raised to 75°C, and the mixture is allowed to stand for 6 hours to allow complexation to occur in the system, and then the temperature is raised to 120°C at a heating rate of 2°C / min and dried for 12 hours, and finally the temperature is raised to 450°C at a heating rate of 2°C / min and calcined for 3 hours to obtain a supported cracking catalyst with a Ni loading rate of 12wt% and a La loading rate of 0.6wt%.
[0061] Preparation Example 2.2
[0062] The preparation method of the supported cracking catalyst is different from that of Preparation Example 1.1 in that, in step II, an auxiliary catalytic substance with a loading rate of 1.0 wt% is also included, specifically:
[0063] II. Preparation of catalyst: Ni(NO3)2·6H2O, Mg(NO3)2·6H2O, anhydrous citric acid and ethylene glycol were dispersed in water to obtain a mixed solution with a Ni(NO3)2·6H2O concentration of 3.4 mol / L, a Mg(NO3)2·6H2O concentration of 0.28 mol / L and anhydrous citric acid concentration of 4.416 mol / L. The amount of ethylene glycol added was 0.866 wt %. Ultrasonic mixing was performed for 10 min, and then an equal volume impregnation method was used to measure step I. The adsorption volume of the cerium-zirconium solid solution obtained in step I is adjusted, and an equal adsorption volume of the mixed solution is added dropwise to the cerium-zirconium solid solution obtained in step I. After standing at room temperature for 24 hours, the temperature is raised to 75°C and continued to stand for 6 hours to allow complexation to occur in the system. The temperature is then raised to 120°C at a heating rate of 2°C / min and dried for 12 hours. Finally, the temperature is raised to 450°C at a heating rate of 2°C / min and calcined for 3 hours to obtain a supported cracking catalyst with a Ni loading rate of 12wt% and a Mg loading rate of 1.0wt%.
[0064] Preparation Example 3.1
[0065] The preparation method of the loaded cracking catalyst is different from that of Preparation Example 2.1 in that, in step II, Mg(NO3)2·6H2O is also added, the molar ratio of Mg(NO3)2·6H2O to La(NO3)3·6H2O is 3:2, and the total concentration of Mg(NO3)2·6H2O and La(NO3)3·6H2O is still 0.17 mol / L. Finally, a loaded cracking catalyst with a total loading rate of Mg and La of 0.6 wt% is obtained. The rest is the same as Preparation Example 2.1.
[0066] Preparation Example 3.2
[0067] The preparation method of the loaded cracking catalyst is different from that of Preparation Example 2.1 in that, in step II, Mg(NO3)2·6H2O is also added, the molar ratio of Mg(NO3)2·6H2O to La(NO3)3·6H2O is 1:6, and the total concentration of Mg(NO3)2·6H2O and La(NO3)3·6H2O is still 0.17 mol / L. Finally, a loaded cracking catalyst with a total loading rate of Mg and La of 0.6 wt% is obtained. The rest is the same as Preparation Example 2.1.
[0068] Preparation Example 3.3
[0069] The preparation method of the supported cracking catalyst is different from that of Preparation Example 3.1 in that in step II, the molar ratio of Mg(NO3)2·6H2O to La(NO3)3·6H2O is 2:4, and the rest is the same as Preparation Example 3.1.
[0070] Preparation Example 4.1
[0071] The preparation method of the loaded cracking catalyst is different from that of Preparation Example 3.1 in that, in step II, the total concentration of Mg(NO3)2·6H2O and La(NO3)3·6H2O is 0.204 mol / L, and a loaded cracking catalyst with a total loading rate of Mg and La of 0.72 wt% is obtained. The rest is the same as Preparation Example 3.1.
[0072] Preparation Example 4.2
[0073] The preparation method of the loaded cracking catalyst is different from that of Preparation Example 3.1 in that, in step II, the total concentration of Mg(NO3)2·6H2O and La(NO3)3·6H2O is 0.23 mol / L, and a loaded cracking catalyst with a total loading rate of Mg and La of 0.82 wt% is obtained. The rest is the same as Preparation Example 3.1.
[0074] Preparation Example 4.3
[0075] The preparation method of the supported cracking catalyst is different from that of Preparation Example 3.1 in that, in step II, the total concentration of Mg(NO3)2·6H2O and La(NO3)3·6H2O is 0.265 mol / L, and a supported cracking catalyst with a total loading rate of Mg and La of 0.92 wt% is obtained. The rest is the same as Preparation Example 3.1.
[0076] Preparation Example 4.4
[0077] The preparation method of the loaded cracking catalyst is different from that of Preparation Example 3.3 in that, in step II, the total concentration of Mg(NO3)2·6H2O and La(NO3)3·6H2O is 0.204 mol / L, and a loaded cracking catalyst with a total loading rate of Mg and La of 0.72 wt% is obtained. The rest is the same as Preparation Example 3.3.
[0078] Comparative Preparation Example 1.1
[0079] The difference from Preparation Example 1.1 is that Zr(NO3)4·5H2O in step I is removed, the amount of Ce(NO3)3·6H2O used is 10 mol, and a cerium solid solution is obtained. The rest is the same as Preparation Example 1.1.
[0080] Comparative Preparation Example 1.2
[0081] The difference from Preparation Example 1.1 is that Ce(NO3)3·6H2O in step I is removed, the amount of Zr(NO3)4·5H2O is 10 mol, and a zirconium solid solution is obtained. The rest is the same as Preparation Example 1.1.
[0082] Comparative Preparation Example 2.1
[0083] The difference from Preparation Example 1.1 is that in step I, the amount of Zr(NO3)4·5H2O used is 5 mol, the amount of Ce(NO3)3·6H2O used is 5 mol, and the rest is the same as Preparation Example 1.1.
[0084] Comparative Preparation Example 2.2
[0085] The difference from Preparation Example 1.1 is that in step I, the amount of Zr(NO3)4·5H2O used is 9.5 mol, the amount of Ce(NO3)3·6H2O used is 0.5 mol, and the rest is the same as Preparation Example 1.1.
[0086] Example 1.1
[0087] A method for preparing renewable energy by photothermal decomposition of biomass in wastewater, comprising the following steps:
[0088] The sludge was dehydrated and crushed to 50 mesh to obtain the starting material with a total weight of 8 kg. 1 kg of co-solvent (coal gangue) and 3 kg of loaded cracking catalyst prepared in Preparation Example 1.1 were added and mixed evenly. The mixture was put into the cracking equipment, and then the cracking equipment was sealed and nitrogen was introduced. The sunlight was absorbed by the heliostat and the reflection channel, and the light was transmitted to the heat absorption device. The cracking equipment was then heated to 525°C in a nitrogen atmosphere. The gaseous and liquid products escaping from the system were collected by the upgrading system, and the renewable energy aromatics and renewable energy CH4 were obtained after separation.
[0089] Example 1.2
[0090] A method for preparing renewable energy by photothermal decomposition of biomass in wastewater, comprising the following steps:
[0091] The sludge was dehydrated and crushed to 50 mesh to obtain the starting material with a total weight of 8 kg. 1.2 kg of co-solvent (coal gangue) and 2.5 kg of the loaded cracking catalyst prepared in Preparation Example 1.1 were added and mixed evenly. The mixture was put into the cracking equipment, and then the cracking equipment was sealed and nitrogen was introduced. The sunlight was absorbed by the heliostat and the reflection channel, and the light was transmitted to the heat absorption device. The cracking equipment was then heated to 550°C in a nitrogen atmosphere. The gaseous and liquid products escaping from the system were collected by the upgrading system, and the renewable energy aromatics and renewable energy CH4 were obtained after separation.
[0092] Example 1.3
[0093] A method for preparing renewable energy by photothermal decomposition of biomass in wastewater, comprising the following steps:
[0094] The sludge was dehydrated and crushed to 50 mesh to obtain the starting material with a total weight of 8 kg. 1.1 kg of co-solvent (coal gangue) and 2.8 kg of the loaded cracking catalyst prepared in Preparation Example 1.1 were added and mixed evenly. The mixture was put into the cracking equipment, and then the cracking equipment was sealed and nitrogen was introduced. The sunlight was absorbed by the heliostat and the reflection channel, and the light was transmitted to the heat absorption device. The cracking equipment was then heated to 500°C in a nitrogen atmosphere. The gaseous and liquid products escaping from the system were collected by the upgrading system, and the renewable energy aromatics and renewable energy CH4 were obtained after separation.
[0095] Examples 2.1-2.3
[0096] A method for treating biomass in wastewater by photothermal decomposition to prepare renewable energy, which is different from Example 1.3 in that the supported decomposition catalyst prepared in Preparation Example 1.1 is replaced by the supported decomposition catalysts prepared in Preparation Examples 1.2-1.4 respectively, and the rest is the same as Example 1.3.
[0097] Examples 3.1-3.9
[0098] A method for treating biomass in wastewater by photothermal decomposition to prepare renewable energy, which is different from Example 1.3 in that the supported decomposition catalyst prepared in Preparation Example 1.1 is replaced by the supported decomposition catalysts prepared in Preparation Examples 2.1-4.4 respectively, and the rest is the same as Example 1.3.
[0099] Example 4.1
[0100] A method for preparing renewable energy from biomass in wastewater by photothermal decomposition, which differs from Example 1.3 in that 1.1 kg of coal gangue is replaced by 0.66 kg of coal gangue and 0.44 kg of calcined coal gangue, and the rest is the same as Example 1.3.
[0101] Example 4.2
[0102] A method for preparing renewable energy from biomass in wastewater by photothermal decomposition, which differs from Example 1.3 in that 1.1 kg of coal gangue is replaced by 0.78 kg of coal gangue and 0.32 kg of calcined coal gangue, and the rest is the same as Example 1.3.
[0103] Example 4.3
[0104] A method for preparing renewable energy from biomass in wastewater by photothermal decomposition, which differs from Example 1.3 in that 1.1 kg of coal gangue is replaced by 0.704 kg of coal gangue and 0.396 kg of calcined coal gangue, and the rest is the same as Example 1.3.
[0105] Example 4.4
[0106] A method for preparing renewable energy from biomass in wastewater by photothermal decomposition, which differs from Example 3.9 in that 1.1 kg of coal gangue is replaced by 0.704 kg of coal gangue and 0.396 kg of calcined coal gangue, and the rest is the same as Example 3.9.
[0107] Comparative Examples 1-4
[0108] The difference from Example 1.3 is that the supported cracking catalyst prepared in Preparation Example 1.1 is replaced by the supported cracking catalysts prepared in Comparative Preparation Examples 1.1-2.2 respectively, and the rest is the same as Example 1.3.
[0109] Comparative Example 5
[0110] The difference from Example 1.3 is that the amount of co-solvent (coal gangue) used is 2 kg, the amount of supported cracking catalyst prepared in Preparation Example 1.1 used is 2 kg, and the rest is the same as Example 1.3.
[0111] Comparative Example 6
[0112] The difference from Example 1.3 is that the amount of the co-solvent (coal gangue) used is 0.5 kg, the amount of the supported cracking catalyst prepared in Preparation Example 1.1 used is 3.5 kg, and the rest is the same as Example 1.3.
[0113] Comparative Example 7
[0114] The difference from Example 1.3 is that the co-solvent (coal gangue) is removed, the amount of the supported cracking catalyst prepared in Preparation Example 1.1 is 4 kg, and the rest is the same as Example 1.3.
[0115] Comparative Example 8
[0116] The difference from Example 1.3 is that the supported cracking catalyst prepared in Preparation Example 1.1 is removed, the amount of co-lysate (coal gangue) used is 4 kg, and the rest is the same as Example 1.3.
[0117] Comparative Example 9
[0118] The difference from Example 1.3 is that the coal gangue is replaced by calcined coal gangue, and the rest is the same as Example 1.3.
[0119] Comparative Example 10
[0120] The difference from Example 1.3 is that the supported cracking catalyst prepared in Preparation Example 1.1 is removed, 1 kg of coal gangue is replaced with 0.704 kg of coal gangue and 0.396 kg of calcined coal gangue, and the rest is the same as Example 1.3.
[0121] Performance Testing
[0122] The proportion of CH4 in the gas phase products and the proportion of aromatic hydrocarbons in the liquid phase products obtained in the examples and comparative examples were determined by gas chromatography, and the results are recorded in Table 2.
[0123] Table 2 Performance test
[0124]
[0125] Data Analysis:
[0126] As can be seen from Table 2, the treatment method in Example 1, the proportion of CH4 in the obtained gas phase product is 73.5-74.9 vol%, and the proportion of aromatics in the liquid phase product is 87.8-88.6 wt%, which proves that the present application uses the co-solvent and the starting material to carry out synergistic photothermal cracking under the catalysis of the supported cracking catalyst, and the co-solvent can promote the conversion of complex organic matter in the starting material into volatile organic matter first, and finally produce a gas phase product rich in CH4 and a liquid phase product rich in aromatics. The supported cracking catalyst can maintain a catalytic activity and stability far exceeding other catalysts when the temperature fluctuates, and has a high selectivity for CH4, which greatly increases the content of CH4 in the gas phase product, and at the same time increases the rate of the thermal cracking reaction process, so that the resource treatment efficiency of biomass in the sewage during the treatment cycle can be maintained at a high level. Among them, the proportion of CH4 in the gas phase product and the proportion of aromatics in the liquid phase product of Example 1.3 are significantly higher than those of Examples 1.1-1.2, which proves that the present application further improves the yield of CH4 and aromatics by strictly controlling the weight ratio of the starting material, the co-solvent and the supported cracking catalyst;
[0127] The difference between Example 2.1-2.3 and Example 1.3 is that the present application replaces the supported cracking catalysts with different cerium-zirconium ratios, and the proportion of CH4 in the gas phase products of Example 2.1-2.3 is significantly lower than that of Example 1.3, which proves that the present application strictly controls the molar ratio of Zr(NO3)4·5H2O and Ce(NO3)3·6H2O to control the molar ratio of Zr and Ce in the final cerium-zirconium solid solution, further improves the catalytic stability of the supported cracking catalyst, can continuously play a good catalytic effect on the methanation reaction, and maintain the CH4 content in the gas phase product stable and high;
[0128] In Examples 3.1-3.2, the present application uses a supported cracking catalyst with an auxiliary catalytic substance. The results show that the proportion of CH4 in the gas phase product and the proportion of aromatic hydrocarbons in the liquid phase product are significantly improved, proving that the present application adds a certain loading rate of auxiliary catalytic substances to the supported cracking catalyst, broadens the reaction activity temperature range of the supported cracking catalyst, and further improves its adaptability to temperature and reaction activity;
[0129] In Examples 3.3-3.5, the proportion of CH4 in the gas phase product and the proportion of aromatics in the liquid phase product are both higher than those in Examples 3.1-3.2, which proves that Mg and La can give full play to the synergistic effect and maximize the catalytic activity of the supported cracking catalyst. At the same time, the reaction activity temperature range of the supported cracking catalyst can be further expanded. When temperature fluctuations occur during the cracking process, the catalytic effect itself can be made more stable, and the yield of aromatics and CH4 can be kept stable and high. In addition, the proportion of CH4 in the gas phase product and the proportion of aromatics in the liquid phase product of Example 3.5 are the most improved, which proves that the present application can optimize the catalytic effect to the maximum extent by strictly controlling the molar ratio of Mg and La;
[0130] The proportion of CH4 in the gas phase product of Example 3.6 and the proportion of aromatic hydrocarbons in the liquid phase product of Example 3.6 in Examples 3.6-3.8 are higher than those in Examples 3.7-3.8, which proves that the present application can significantly improve the catalytic ability of the supported cracking catalyst by continuously adjusting the loading rate of the auxiliary catalytic substance on the supported cracking catalyst. If the loading rate is too high, it will affect the catalytic effect of Ni. If the loading rate is too low, it will not have an effective auxiliary effect.
[0131] The proportion of aromatics in the liquid products of Examples 4.1-4.3 is significantly higher than that of Example 1.3, which proves that the present application can more significantly promote the generation of aromatics by adding calcined coal gangue to the co-solvent, and the proportion of aromatics in the liquid products and the proportion of CH4 in the gas products of Example 4.3 are significantly higher than those of Examples 4.1-4.2, which proves that the present application achieves an optimal balance in the generation-promoting effect of the co-solvent on CH4 and aromatics by strictly controlling the weight ratio of coal gangue to calcined coal gangue, and both are at a relatively high level, and at this time, the synergistic effect of the co-solvent and the supported cracking catalyst is better, so that the proportion of CH4 and aromatics finally generated in the product is further improved;
[0132] The proportion of CH4 in the gas phase product and the proportion of aromatic hydrocarbons in the liquid phase product of Comparative Examples 1-4 are lower than those in Example 1.3, which proves that the supported cracking catalyst of the present application can greatly promote the methanation reaction in the system, increase the content of CH4 in the gas phase product, and at the same time increase the rate of the thermal cracking reaction process, so that the resource treatment efficiency of biomass in sewage can be maintained at a high level during the treatment cycle;
[0133] The proportion of CH4 in the gas phase product and the proportion of aromatics in the liquid phase product of Comparative Examples 5-6 are both lower than those in Example 1.3, which proves that the present application further improves the yield of CH4 and aromatics by strictly controlling the weight ratio of the starting material, the co-solvent and the supported cracking catalyst;
[0134] The proportion of aromatic hydrocarbons in the liquid phase product of Comparative Example 7 is particularly lower than that in Example 1.3, and the proportion of CH4 in the gas phase product of Comparative Example 8 is particularly lower than that in Example 1.3, which proves that the co-solvent and the supported cracking catalyst of the present application have a significant synergistic effect, and can jointly ensure that the composition of the cracking product is more stable, so as to obtain more high-value energy;
[0135] The proportion of CH4 in the gas phase product of Comparative Examples 9-10 is particularly lower than that in Example 1.3, while the proportion of aromatic hydrocarbons in the liquid phase product is not much different from that in Example 1.3. Overall, the resource utilization effect of Examples 9-10 is far inferior to that of Example 1.3, which proves that the present application can effectively increase the proportion of CH4 while increasing the proportion of aromatic hydrocarbons by utilizing the good synergistic effect of coal gangue and supported cracking catalyst.
[0136] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A method for preparing renewable energy from biomass in wastewater by photothermal decomposition, characterized in that: The following steps are involved: The sludge is dehydrated and crushed to obtain a starting material, and a co-solvent and a supported cracking catalyst are added, mixed evenly, and then heated to 500-550° C. The gaseous products and liquid products escaping from the system are collected, and the renewable energy is obtained after separation. The weight ratio of the starting material, the co-solvent and the supported cracking catalyst is 80: (10-12): (25-30), the co-solvent includes coal gangue, the carrier in the supported cracking catalyst is a cerium-zirconium solid solution, the main catalytic substance is Ni, and the loading rate of Ni is 12-13wt%, and the supported cracking catalyst also includes an auxiliary catalytic substance with a loading rate of 0.72wt%, and the auxiliary catalytic substance includes Mg and La with a molar ratio of 2:4; The cerium-zirconium solid solution is prepared by the following method: Disperse Zr(NO3)4·5H2O and Ce(NO3)3·6H2O in a molar ratio of (3-9):1 in water, and add them together with ammonia water into a polyethylene glycol solution under stirring to stabilize the pH value in the system at 10.5-11.5, stir, add ethanol, and heat to 65-75°C at a heating rate of 2-2.2°C / min, continue stirring, then keep the temperature unchanged, age, filter, wash, freeze-dry, and calcine to obtain a cerium-zirconium solid solution.
2. The method for preparing renewable energy from biomass in wastewater by photothermal decomposition according to claim 1, characterized in that: The weight ratio of the starting material, the co-lysate and the supported cracking catalyst is 80:11:
28.
3. The method for preparing renewable energy from biomass in wastewater by photothermal decomposition according to claim 1, characterized in that: The molar ratio of Zr(NO3)4·5H2O to Ce(NO3)3·6H2O is 4:
1.
4. The method for preparing renewable energy from biomass in wastewater by photothermal decomposition according to claim 1, characterized in that: The co-solvent includes coal gangue and calcined coal gangue in a weight ratio of 5:(2-3).
5. The method for preparing renewable energy from biomass in wastewater by photothermal decomposition according to claim 4, characterized in that: The weight ratio of the coal gangue to the calcined coal gangue is 5:2.8.
Citation Information
Patent Citations
Catalyst carrier for biomass pyrolysis, catalyst and preparation method of catalyst carrier
CN113117710A
Additive for pyrolysis of hazardous waste sludge, and pyrolysis treatment method
CN113666597A
Monoatom-loaded cerium-zirconium solid solution catalyst as well as preparation method and application thereof
CN114471527A
Novel method for preparing ceramsite through synergistic co-treatment of coal gangue and sludge
CN116639993A